Possible Association of Periodontal Diseases With Helicobacter pylori Gastric Infection: A Systematic Review and Meta-Analysis - López-Valverde, Nansi; Macedo de Sousa, Bruno; López-Valverde, Antonio; Suárez, Ana; Rodríguez, Cinthia; Aragoneses, Juan Manuel (Frontiers in Medicine, 2022)
Gastroesophageal infection by Helicobacter Pylori, as well as periodontal diseases, are a type of infectious pathologies prevalent in a high percentage of the human population. Some research has demonstrated the possible association of both pathologies, through studies based on the presence of Helicobacter Pylori bacteria in dental bacterial plaque, periodontal pockets and saliva. This presence would be responsible for recolonization and chronic infection by the bacteria. However, there are serious discrepancies among researchers, reporting figures ranging from 40% to 97% on the presence of Helicobacter Pylori in the oral cavity, such discrepancies being attributed to different sampling procedures and different detection methodologies of the microorganism in dental plaque, since some studies have criticized the polymerase chain reaction as an inadequate method of detection. Therefore, due to the scarce conclusive evidence supporting the role of the oral cavity as a reservoir, there is great confusion among the scientific community about the possible association between periodontal diseases and gastric infection by Helicobacter Pylori, giving rise to the objective of our review and meta-analysis, which has tried to identify and analyze the clinical studies that determine the direct correlation between both pathologies.